Inseticidas para o controle de insetos-praga na cultura da cana-de-açúcar: classificações e modalidades - Souza, Allan Marcel Borguete de (Universidade Federal de São Carlos, 2023)
The sugarcane culture presents relevant economic importance in the Brazilian agribusiness. Among the various limiting factors in sugarcane production, pest insects are prominent, requiring the adoption of efficient control. The increasing search for alternatives in integrated pest management has demanded more and more knowledge from producers, seeking alternatives that are economically viable, environmentally accepted, and have high control efficiency. This work was carried out with the objective of surveying the phytosanitary products registered at the Ministry of Agriculture, Livestock, and Supply (MAPA), aiming to point out, in a targeted way, the active ingredient, mechanism of action, mode of action, toxicological class, application modality, target insects, selectivity, active ingredient dose, and withdrawal period of products available for sugarcane. The survey was carried out through the database of MAPA, made available on the AGROFIT website, where information was obtained through the formulated products category, using filters for insecticides, biological control agents, and microbiological insecticides for sugarcane culture. All data collected from October 2020 to March 2022 were inserted into an MS-Excel program table, making it possible to consult the necessary information for the study.
Insecticides for the control of pests in sugarcane culture: classifications and action modes
Keywords: Controle químico; Seletividade; Mecanismo de ação; Pragas; Cana-de-açúcar; Chemical control; Selectivity; Mechanism of action; Pests; Sugarcane; CIENCIAS AGRARIAS::AGRONOMIA::FITOSSANIDADE